2008
DOI: 10.1016/j.humimm.2008.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus-specific CD8+ T-cell responses target a group of epitopes without a strong immunodominance hierarchy in humans

Abstract: Immunization with vaccinia virus (VACV) resulted in long-lasting protection against smallpox and successful global eradication of the disease. VACV elicits strong cellular as well as humoral immune responses. Although neutralizing antibody is essential for protection, cellular immunity seems to be more important for recovery from infection in humans. We analyzed the immunodominance hierarchy of 73 previously identified VACV human CD8 + T cell epitopes restricted by HLA-A1, A2, A3, A24, B7 or B44 alleles or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…While this may be a function of the high levels of challenge dose used in the study, it is more likely an indication of differences in the MVA-induced immune response, which fail to constrain viral replication before the secondary viremia, and seeding of the skin, with virus. In OPXV infections, examination of the effects and interactions of the humoral and cellular responses induced by smallpox vaccines is an active area of research (51,52,73). NAbs appear to be more necessary for protection from challenge than cellular responses (9,15,17,54,56), but there is compelling evidence that intramuscular administration of MVA protects B cell-deficient mice (79), indicating that MVA can protect irrespective of Abs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this may be a function of the high levels of challenge dose used in the study, it is more likely an indication of differences in the MVA-induced immune response, which fail to constrain viral replication before the secondary viremia, and seeding of the skin, with virus. In OPXV infections, examination of the effects and interactions of the humoral and cellular responses induced by smallpox vaccines is an active area of research (51,52,73). NAbs appear to be more necessary for protection from challenge than cellular responses (9,15,17,54,56), but there is compelling evidence that intramuscular administration of MVA protects B cell-deficient mice (79), indicating that MVA can protect irrespective of Abs.…”
Section: Discussionmentioning
confidence: 99%
“…Although smallpox has been eradicated (5), orthopoxviruses (OPXVs), such as variola virus (VARV) (6, 32), monkeypox virus (MPXV) (3, 10, 57), vaccinia virus (VACV) (4, 76), and others (53,68,77), are a continuing public health concern (61, 67). Due to cellular and humoral protective effects (7,15,16,46,73), the traditional live VACV-based smallpox vaccines provide cross-protection against multiple OPXV threats (48). Unfortunately, the cessation of routine vaccination (37) has left much of the global population fully susceptible to OPXV infections (34), and the adverse effects of first-and secondgeneration vaccines (78) coupled with increases in the global immunocompromised population (59) underline the need for continued development and testing of safer smallpox vaccines (30).…”
mentioning
confidence: 99%
“…Notably, even pathogens with relatively small proteomes, e.g., influenza virus, generate broad TCD8 responses in humans (53), and those with large proteomes, e.g., VACV, elicit a more complex response (28,29). Hence, we would predict the actual breadth of the TCD8 response to complex pathogens -such as Plasmodium or Mycobacterium spp., which surprisingly has never been determined -to be much more complex than those described so far.…”
Section: Figurementioning
confidence: 99%
“…Interrogation of computationally predicted epitopes revealed that humans and mice recognize numerous epitopes by VACV-immune TCD8; humans recognize these epitopes in a variegated, i.e., partially overlapping, manner (27)(28)(29)(30)(31). Nevertheless, due to the current limitations of bioinformatics prediction approaches, identification of viral determinants that are efficiently presented in vivo and initiate protective TCD8 responses remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation